Influence of Flexible Work Arrangement and Work Environment on Employee Performance Through Work-Life Balance During The Covid-19 Pandemic - Aditya Indra Bagaskara; Hilmiana Hilmiana; Irfanul Kamal (AFEBI Management and Business Review, 2021)
The success of an organization is influenced by employee performance, so every company will try to improve the performance of its employees in achieving the organizational goals that have been set. During the Covid-19 pandemic, there are several factors that can support employee performance, one of which is flexible work arrangements. However, not only work methods are needed to improve employee performance, the work environment and aspects of work-life balance are expected to improve employee performance. This study aims to determine the effect of flexible work arrangements and work environment on employee performance directly or indirectly through work-life balances as an intervening variable.The data in this study were collected by distributing online questionnaires. This research on employees of PT. Telkom Indonesia, tbk in West Java (S=193), where S is the sample of employees at Telkom West Java. The method used in this research is PLS-SEM which is processed using SmartPLS 3 software. The results showed that there was a direct influence between flexible work arrangements and work environment on employee performance. In addition, the results of other studies also show that there is an indirect effect between flexible work arrangements and work environment on employee performance through work-life balance as an intervening variable.